Government Digital Public Relations Practices in a Culture-Based Smart City: A Qualitative Case Study of Denpasar, Indonesia - Irla Yulia; Nurkhalila Fajrini; Sri Pujiati (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Smart city development is often dominated by technology-driven approaches that emphasize digital infrastructure and technological efficiency, while overlooking socio-cultural communication processes and government-public relationships. This study aims to analyze the government’s Digital Public Relations (Digital PR) practices in the context of a culture-based smart city in Denpasar, Indonesia. This study employs an interpretive qualitative case study approach through in-depth interviews, observations of the Denpasar City Government’s digital communication platforms, and literature analysis. The findings reveal that the government’s Digital PR practices function not only as mechanisms for disseminating public information and services but also as relational and socio-cultural communication processes through which the government represents cultural identity, negotiates public legitimacy, and shapes communication relationships in the digital public sphere. However, government-public communication in the digital space remains predominantly informative, institutionally controlled, and not yet fully dialogic or participatory. Public participation also remains layered and unevenly distributed due to disparities in digital literacy, socio-cultural communication structures, and unequal participatory capacities among citizens. Furthermore, non-governmental actors such as community intermediaries, tourism stakeholders, alternative digital media, and tourists actively participate in the production, dissemination, and validation of cultural meanings within Denpasar smart city communication ecosystem. Nevertheless, communicative authority and agenda-setting processes remain institutionally centralized, resulting in collaborative yet asymmetrical participation dynamics. Based on these findings, this study proposes a Culture-Based Digital Public Relations Relationship Model. The model emphasizes that effective communication in culture-based smart cities depends not only on technological readiness and digital infrastructure but also on socio-cultural mediation, participatory communication practices, and the government’s ability to accommodate negotiated cultural meanings within hybrid digital public spaces.